Changes in Sleep Quality Before and During the COVID-19 Pandemic: The Role of Psychosocial Vulnerability - Jun-Sang Sunwoo (Journal of Sleep Medicine, 2026)
Objectives: The coronavirus disease 2019 (COVID-19) pandemic significantly disrupted daily life and sleep habits. In this study, we aimed to investigate changes in sleep quality before and during the COVID-19 pandemic using a large prospective cohort and identify factors associated with deterioration in sleep quality.Methods: We analyzed 60,056 participants (age, 41.32±6.64 years; female, 23.5%) who completed the Pittsburgh Sleep Quality Index (PSQI) before and during the COVID-19 pandemic. Poor sleep quality was defined as a global PSQI score >5, and sleep quality deterioration was considered a transition from good to poor sleep quality. Multivariable logistic regression analysis was performed to identify factors associated with sleep quality deterioration.Results: The global PSQI score did not change significantly before and during the COVID-19 pandemic (4.61±2.28 vs. 4.59±2.33; p=0.110). However, sleep quality deteriorated in 15.7% of the participants and improved in 16.5%. After adjusting for confounders, anxiety showed the strongest association with sleep quality deterioration (adjusted odds ratio [aOR]=2.426 for mild-to-moderate anxiety; aOR=3.633 for severe anxiety). Higher occupational stress (aOR=1.028), daytime sleepiness (aOR=1.983), unmarried status (aOR=1.365), and female sex (aOR=1.209) were also independently associated with sleep deterioration, whereas higher education level conferred protection (aOR=0.789) against sleep disruption.Conclusions: Although average sleep quality remained unchanged during the COVID-19 pandemic, a substantial proportion of adults experienced deterioration in sleep quality. Psychosocial vulnerability may play an important role in sleep quality deterioration during public health crises.